04.16 Tnf/tnfr2 signalling in mesenchymal cells of joints and aortic heart valves is aetiopathogenic for comorbid arthritis and heart valve disease developing in the tnfΔare/+ mouse model. (1st March 2017) - Sakkou, Maria; Denis, Maria C; Chouvardas, Panagiotis; Prados, Alejandro; Karagianni, Niki E; Ntari, Lydia; Kollias, George
Abstract : Background: Chronic inflammatory diseases, such as Rheumatoid arthritis (RA) and Inflammatory Bowel Disease (IBD) are often co-manifested with additional comorbidities. Studies performed in the established TNF ΔARE/+ mouse model of TNF dependent RA and Crohn's-like IBD, have demonstrated that stromal cells in the joint and the gut are primary and sufficient targets of TNF leading to the development of these two pathologies. Valvular heart disease (VHD) is one of the most common comorbid conditions in RA patients, that frequently leads to heart failure and premature death. We have recently observed that VHD is also displayed in the TNF ΔARE/+ mouse model and our current aim has been to identify whether TNF signalling in stromal cells of the heart play also a role in regulating the VHD pathology similarly to what has been shown in the joint-gut axis. To this end we have used ColVI-Cre mice (specific for mesenchymal cells) and dissected genetically the role of TNFR2 in the stroma of the TNF ΔARE/+ mouse model by assessing its function in RA and the VHD comorbidity. Materials and methods: Mesenchymal cells specific deletion of TNFR2 was achieved by crossing TNF ΔARE/+ to ColVICre/p75 f/f . We further used histopathological analysis and cell isolation, characterisation, signalling analysis and RNAseq expression profiling analysis to decipher the pathologic mechanisms. Results: Interestingly, we found that stroma-specific TNFR2 deletion leads to amelioration of RA and VHD pathologies. These results point to a common role of stroma-expressing TNFR2 in RA and VHD. Furthermore, we identified that isolated stromal cells from joint (SFs) and aortic heart valve (VICs) lacking TNFR2, failed to acquire pathogenic 'activated phenotypes' and display increased expression of the anti-inflammatory IL1RA which correlated with increased AKT signalling. Comparative RNAseq experiments performed in SFs and VICs lacking TNFR2 showed that the majority of deregulated pathways in TNF ΔARE/+ are reversed to normal levels. Conclusion: Taken together, our data demonstrate that the RA and VHD comorbidities developing in the TNF ΔARE/+ mouse model, share common cellular mechanisms converging at the TNF/TNFR2 dependent activation of their mesenchymal stroma.